Moderated online social therapy for depression relapse prevention in young people: pilot study of a 'next generation' online intervention. Issue 4 (17th June 2016) - Rice, Simon; Gleeson, John; Davey, Christopher; Hetrick, Sarah; Parker, Alexandra; Lederman, Reeva; Wadley, Greg; Murray, Greg; Herrman, Helen; Chambers, Richard; Russon, Penni; Miles, Christopher; et al.
Abstract: Aim: Implementation of targeted e‐mental health interventions offers a promising solution to reducing the burden of disease associated with youth depression. A single‐group pilot study was conducted to evaluate the acceptability, feasibility, usability and safety of a novel, moderated online social therapy intervention (entitled Rebound) for depression relapse prevention in young people. Methods: Participants were 42 young people (15–25 years) (50% men; mean age = 18.5 years) in partial or full remission. Participants had access to the Rebound platform for at least 12 weeks, including the social networking, peer and clinical moderator and therapy components. Results: Follow‐up data were available for 39 (92.9%) participants. There was high system usage, with 3034 user logins (mean = 72.2 per user) and 2146 posts (mean = 51.1). Almost 70% of users had ≥10 logins over the 12 weeks, with 78.5% logging in over at least 2 months of the pilot. A total of 32 (84%) participants rated the intervention as helpful. There was significant improvement between the number of participants in full remission at baseline ( n = 5; none of whom relapsed) relative to n = 19 at 12‐week follow‐up ( P < 0.001). Six (14.3%) participants relapsed to full threshold symptoms at 12 weeks. There was a significant improvement to interviewer‐rated depression scores (Montgomery–Asberg Depression Rating Scale (MADRS); P = 0.014, d = 0.45) and a trend for improved strength use ( P = 0.088, d = 0.29). The single‐group design and 12‐week treatment phase preclude a full understanding of the clinical benefits of the Rebound intervention. Conclusions: The Rebound intervention was shown to be acceptable, feasible, highly usable and safe in young people with major depression.